Perspectives on the Yi of Southwest China - Harrell, Stevan (Studies on China ;, 2001)
Nearly seven million Yi people live in Southwest China, but most educated people outside China have never heard of them. This book brings this little-known part of the world to life, describing its history, traditional society, and recent social changes.